Interaction between age and health conditions in the intention to be vaccinated against COVID-19 in Thailand - Sakun Boon-itt; Nopadol Rompho; Sompong Jiarnkamolchurn; Yukolpat Skunkan (Taylor & Francis Group, 2021)
To study the sociodemographic factors as well as the interaction between age groups and health conditions in relation to the intention of being vaccinated against coronavirus disease 2019 (COVID-19) in Thailand. A cross-sectional survey was conducted during the "third wave" of the COVID-19 pandemic in Thailand (March to April 2021). The survey was uploaded and administered via the online survey platform of Google™. Thai citizens aged >18 years completed the survey. All factors that predicted the vaccine intention (VI) among participants were measured and analyzed using logistics regression and cross-tabulation. Among 862 participants, 55.6% said they were likely to get a COVID-19 vaccine. From the finding of the logistic regression, men were more likely to be vaccinated than women. Respondents with more than three health conditions were less likely to get vaccinated compared with those without any health conditions. People at a higher risk of health conditions had the lowest VI in any age group. Among the older age group, the number of health conditions affected the VI. The potential harmful side effects of a COVID-19 vaccine was the main reason for vaccine hesitancy. Overall, ~56% of respondents to an online questionnaire intended to become vaccinated against COVID-19. The older age group with a high risk of health conditions had the lowest VI even though this group should get the vaccine first. Therefore, there is an urgent need to design an education strategy to overcome such vaccine hesitancy.